2006 International Conference on Computer Engineering and Systems 2006
DOI: 10.1109/icces.2006.320463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ad Hoc Routing Protocols in Real Simulation Environments

Abstract: In order to conduct meaningful performance analysis of routing algorithms in the context of Mobile Ad Hoc Networks (MANETs), it is essential that the underlying mobility model on which the simulation is based reflects realistic mobility behavior. In this paper, the most widely known ad hoc routing protocols will be simulated in our proposed real simulation environment to figure out the effect of real environmental simulation on ad hoc routing protocols and to show the robustness of current simulation output re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Ad hoc networks have two forms; one is static ad hoc networks (SANET), and the other is called mobile ad hoc network (MANET). Commercial implementation of ad hoc networks has become possible due to the development of new technology such as 802.11 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ad hoc networks have two forms; one is static ad hoc networks (SANET), and the other is called mobile ad hoc network (MANET). Commercial implementation of ad hoc networks has become possible due to the development of new technology such as 802.11 [9].…”
Section: Introductionmentioning
confidence: 99%
“…So many research of MANET has been focused on the development of the routing protocols. Typical examples of this research are shown in the references [2,3,4]. However, in this paper, we focus on the performance of mobile ad hoc network over TCP (Transport Control Protocol).…”
Section: Introductionmentioning
confidence: 99%